Performance Appraisal and Employee Engagement: Does Tenure Matters? Evidence from South-West Nigeria - Ajibola, Kolawole Sunday; Mukulu, Elegwa; Simiyu, Alice (Quest Journal of Management and Social Sciences, 2019)
Background: The level of employee engagement globally is declining. Evidences points to low level of employee engagement in Nigeria. In this study, performance appraisal and performance appraisal feedback are hypothesized as factors that increase the level of employee engagement. Objective: The objective of the study was to investigate the influence of performance appraisal and performance appraisal feedback on the employee engagement among workers in South-West Nigeria. Methods: The study adopted descriptive research approach. Respondents were sampled from employees of one State University, wire industries, and oil and gas sector in Osun State capital, Nigeria. Stratified and simple random sampling techniques were used to select 250 respondents. The questionnaire was used for data collection. Only 139 (54.51%) questionnaires were found useful for the analysis. Descriptive statistics, correlation and regression analyses were used for the data analysis. Results: The study found out that performance appraisal had positive significant influence on employee engagement but the relationship between performance appraisal feedback and employee engagement was found to be statistically insignificant. Tenure was found to moderate the influence on the relationships. Conclusions: Based on the findings of the study, the study concluded that employee tenure was an important moderator in the relationship between performance appraisal, performance appraisal feedback and employee engagement. Implications: The implication of the findings of this study was that employee characteristics are important factors for the consideration of Human resource practitioners for organization effectiveness and productivity. Recommendations: The paper recommended that HR managers should pay more attention to the employee metrics in implementing HR policies.